Analisis Kelayakan Bisnis pada Usaha Produksi Tempe Rumahan dalam Perfektif Islam - Dwi Cantika Putri; Jahara Siregar (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
One of the potential micro businesses in Indonesia is the tempe industry. Many people in this country consume tempeh as a famous meal replacement. Therefore, tempe production plays an important role in meeting the demand for tempe in the Indonesian domestic market. Due to a lack of resources, tempe production is carried out on a small scale. This promising business deserves to be expanded. A feasibility study is a thorough evaluation of a business plan or businesses that are currently operating. The purpose of this study is to define business conditions and determine whether a company is feasible or not to be considered in the various aspects studied. Homemade tempeh production business located on Jl. Helvetia market 4 is the research location. The research method is a qualitative descriptive approach. The method used in data collection includes direct observation at the tempe production site, which is located on Jl. Helvetia pasar 4, and direct interviews with tempe business owners. In addition, documentation from observations and interviews was collected in written and video form.